Auditory Steady-state Responses at multiple frequencies and their value in the objective assessment of hearing - Pérez Ábalo, María Cecilia; Torres Fortuny, Alejandro; Savio López, Guillermo; Eimil Suarez, Eduardo (Auditio, 2021)
One of the main objectives in conducting an electroaudiometric examination is to obtain a specific frequency evaluation of the audibility thresholds. In recent decades, multiple technical proposals have been made based on the recording of Auditory Evoked Potentials (AEP). They are not affected by sedation or sleep and can be detected at stimulation intensities very close to the threshold of audibility. The aforementioned advantages have made it a useful tool for objective hearing evaluation. However, this technique has certain limitations from the electroaudiometric point of view, mainly due to the lack of specified frequency of said response. Auditory Steady State Responses (ASSR) by isolated tonal stimuli and at stimulation frequencies between 75 and 110 Hz have been proposed as a valid alternative for performing a specific frequency audiometry. This type of response represents the synchronous discharge of the brain stem neurons, which follow the modulation frequency of the stimulus that gives rise to them. There have been multiple authors who in recent years and using this type of response have obtained reliable estimates of the tonal audibility threshold, both in healthy children and adults and in hard of hearing subjects. This technique has multiple advantages over transient PEAs in determining specific thresholds in frequency: 1) Given the periodicity of the response, it can be represented in the frequency domain, thus minimizing the complexity of its measurement, 2) The acoustic stimulus used is more specific in frequency, 3) Due to the rectification properties of the cochlea, the response caused by an amplitude modulated tone is represented as a spectral peak at the modulation frequency, 4) These peaks Spectrals can be detected using different frequency domain statistics. Despite the advantages described above, obtaining a complete audiogram using PEAee triggered by isolated tonal stimuli can be time consuming. More recently, an optimized variant of the ASSR between 75 and 110 Hz has been proposed with the simultaneous use of multiple tones modulated in amplitude. Given the fact that each carrier tone is modulated with a different frequency, multiple tones can then be added together, forming a complex tone composed of multiple tones modulated in amplitude. Using then as a stimulus, a mix composed of tones of 500, 1000, 2000 and 4000 Hz we can simultaneously activate and evaluate these four frequency regions of the cochlea. On the other hand, these complex stimuli can be presented binaurally, evaluating both ears simultaneously. PEAee caused by multiple amplitude-modulated tones have been used with encouraging results in the objective determination of audibility thresholds in children and adults, hearing-impaired patients, and in the early detection of hearing defects. This article summarizes some basic concepts, as well as their clinical applications.